THE EFFECT OF SCIENCE AND TECHNOLOGY AND QUALITY OF HUMAN RESOURCES ON THE PROCESSING OF HIGH ECONOMIC VALUE WATER HYACINTH IN LAKE TEMPE, WAJO REGENCY - Andi Nuzul Akbar; Nurdin Brasit; Andi Reni (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This study aims to analyze the influence of science and technology and the quality of human resources in the processing of high economic value water hyacinth in Lake Tempe, Wajo Regency. This research is a type of quantitative research with primary data collection. The sample used is the community around Lake Tempe with the age of 20-39 years, as many as 100 respondents. Data analysis is carried out through stages: collecting data through a questionnaire, and visiting the field directly in order to provide a clear picture of the problem under study. Testing the hypothesis of this study using multiple linear regression data analysis. Data were analyzed using SPSS 23 software. This study states that: (1) science and technology on water hyacinth are of high economic value, with increasing science and technology, economic value is increasing. (2) The quality of human resources has a positive and significant effect on water hyacinth with high economic value, with the increase in the quality of human resources, the economic value is increasing. (3) Simultaneously science and technology and human resources quality have a positive influence on high economic value, partially science and technology, and human resources quality have a positive effect on high economic value. (4) science and technology variable is a more dominant influence on water hyacinth with high economic value.